The role of small extracellular vesicles in spreading and inhibiting arthropod-borne diseases - Owliaee, Iman; Khaledian, Mehran; Shojaeian, Ali; Boroujeni, Armin Khaghani (German Medical Science GMS Publishing House, 2024)
Arthropod-borne diseases (ABDs) refer to a group of viral pathogens that affect a wide range of vertebrate hosts, including humans and non-human primates. In addition to being transmitted by mosquitoes and ticks, arthropods can also spread pathogens that cause severe human diseases. On the other hand, extracellular vesicles (EVs) can serve as cross-placental drug delivery vehicles (DDVs) to the fetus and even as antigen-presenting cells (APCs). To this end, the current review aimed to examine the role of small EVs (sEVs) in the transmission and inhibition of arthropod-borne viruses, also known as arboviruses. First, a deeper understanding of the mechanistic aspects of how these vesicles function during insect-pathogen interactions is required. Next, scalability and yield optimization must be addressed while introducing EV-based therapeutics on an industrial scale in order to implement them effectively. Finally,it is recommended to consider that sEV-mediated transfer plays a crucial role in the spread of ABDs. This is because it transfers pathogenic agents between cells within vectors, resulting in subsequent transmission to hosts. Consequently, sEVs provide potential targets for the development of novel therapies that inhibit pathogen replication or reduce arthropod vector populations. Future research in this area should emphasize how these vesicles function within host-vector systems, using advanced imaging techniques - such as high-resolution microscopy (HRM) - and cost-effective methods, in order to produce sufficient quantities for large-scale implementation.